Birth wind and fire: raising awareness to operating room fires during delivery. (12th April 2013) - Wolf, Omer; Weissman, Oren; Harats, Moti; Farber, Nimrod; Stavrou, Demetris; Tessone, Ariel; Zilinsky, Isaac; Winkler, Eyal; Haik, Josef
Abstract: Objective : We researched whether the obstetric operating room (OR) qualified as a fire-risk environment so as to take preventive measures accordingly. Methods : We analyzed a series of iatrogenic burns inflicted during birth by collecting clinical data and comparing it with known OR fire risk factors and with other factors that repeated in all cases in search of unique characteristics of the obstetric OR. Results : All three cases shared in common the same type of oxygen-rich open ventilation system, alcohol-based prepping solution, and the hastiness of cesarean delivery while spontaneous vaginal delivery was already in progress. Conclusion : The obstetric OR is, as suspected, a fire-prone zone in more ways than the regular OR. Therefore, preventive measures should be undertaken and awareness for the possibility for such occurrences should be raised.